Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Estimation of free fatty acid content in oils, fats, and biodiesel by (1)H NMR spectroscopy - Satyarthi, Jitendra K.; Srinivas, D.; Ratnasamy, Paul (Energy & Fuels, 2009)
A novel (1)H NMR method for the quantification of free fatty acid (FFA) content in vegetable oils, animal fats, and biodiesel is reported. Nonedible oils and animal fats, which are increasingly being explored as cheaper, renewable feed stocks for biodiesel production by transesterification with methanol, contain a significant amount of FFA along with other acidic impurities. The (1)H NMR spectroscopic method is found to be more accurate than the conventional titrimetric analysis for the estimation of FFA content especially in those cases where acidic entities other than the FFA are also present in the feedstock. The titrimetric methods provide a gross acid value which corresponds to that of FFA and other acidic impurities. Our NMR method provides the FFA content exclusively. In the case of refined edible oils (wherein the other acidic impurities are negligible), the results obtained from the (1)H NMR method are comparable with those from the titrimetic analysis.

Esterification of fatty acids with glycerol over Fe-Zn double-metal cyanide catalyst - Kotwal, Mehejabeen; Deshpande, Suvarna S.; Srinivas, D. (Catalysis Communications, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complex exhibits high catalytic activity for esterification of fatty acids (FA) with glycerol. DMC catalysts with varying acidities were prepared by synthesizing the material at four different temperatures (10, 25, 50 and 80 degrees C). The catalyst prepared at 50 degrees C exhibited highest catalytic activity. Catalytic activity of DMC was influenced by both acidity and surface area. Complete conversion of FA was achieved at 140-200 degrees C under atmospheric pressure. Chain length of FA was found to influence the rate of reaction and product selectivity. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid-catalyzed reaction; Double-metal cyanide (DMC); Esterification of fatty acid; Fatty acid glycerides; solid acid catalyst